On Glasgow and Edinburgh - Crawford, Robert, 1959- (Belknap Press of Harvard University Press, 2013)
A mere forty miles apart, these cities have enjoyed a scratchy rivalry since wistful Edinburgh lost parliamentary sovereignty and defiant Glasgow came into its industrial promise. Crawford brings them to life between the covers of one book, in a tale that mixes novelty and familiarity, as Scotland's cultural capital and largest commercial city do.